The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1007/s10578-015-0603-6
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Depressive Symptoms and Toddler Behavior Problems: The Role of Maternal Sensitivity and Child Sex

Abstract: Increasing evidence suggests that maternal depression during pregnancy is associated with child behavioral outcomes even after accounting for later maternal depression. The purpose of this study was to examine various mechanisms, including maternal sensitivity, neonatal problems, and concurrent maternal depression, that might explain the association between prenatal maternal depressive symptoms and toddler behavior problems. Young, low income, African American mothers (n = 196) were interviewed during pregnanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(64 citation statements)
references
References 69 publications
3
58
0
3
Order By: Relevance
“…Data from the Growing Up in Singapore Towards Healthy Outcomes (GUSTO) cohort ( N  = 258) showed that maternal prenatal depressive symptoms were positively associated with both internalizing and externalizing symptoms at age 2 among girls, but only internalizing symptoms in boys [61•]. In a study of young African-American mothers and their offspring ( N  = 196), prenatal depressive symptoms were indirectly associated with increased child social/emotional problems at age 2 through postnatal maternal depressive symptoms and maternal parenting sensitivity, but this effect was significant only among boys [73]. Similarly, a community-based cohort study ( N  = 885) found a significant interaction between prenatal maternal depression and child sex in predicting a broad measure of social-emotional well-being at age 7: Prenatal maternal depression was associated with much higher levels of emotional-behavioral problems among boys and was not significant for girls [40].…”
Section: Resultsmentioning
confidence: 99%
“…Data from the Growing Up in Singapore Towards Healthy Outcomes (GUSTO) cohort ( N  = 258) showed that maternal prenatal depressive symptoms were positively associated with both internalizing and externalizing symptoms at age 2 among girls, but only internalizing symptoms in boys [61•]. In a study of young African-American mothers and their offspring ( N  = 196), prenatal depressive symptoms were indirectly associated with increased child social/emotional problems at age 2 through postnatal maternal depressive symptoms and maternal parenting sensitivity, but this effect was significant only among boys [73]. Similarly, a community-based cohort study ( N  = 885) found a significant interaction between prenatal maternal depression and child sex in predicting a broad measure of social-emotional well-being at age 7: Prenatal maternal depression was associated with much higher levels of emotional-behavioral problems among boys and was not significant for girls [40].…”
Section: Resultsmentioning
confidence: 99%
“…The socioemotional well‐being of infants and young children is tied to the well‐being of their caregivers and the families with whom they live. Caregiver's depression has a harmful impact on child's SED, with possible interpretations including (a) depression affected interactions and attachment security (Carter et al., ; Martins & Gaffan, ; Mason, Briggs, & Silver, ; Roberts, Locasale‐Crouch, Hamre, & Decoster, ); (b) depression decreases a caregiver's sensitivity to child's needs and compromises the ability to provide stimulating and proactive parenting (Edwards & Hans, ; Esposito, Manian, Truzzi, & Bornstein, ; R. Feldman et al., ; Wilson & Durbin, ); and (c) depression is associated with negative parenting behavior (Carter et al., ; Kiernan & Huerta, ; Lovejoy, Graczyk, O'Hare, & Neuman, ), such as neglectful care and harsh discipline.…”
Section: Discussionmentioning
confidence: 99%
“…Research addressing the mediating role of parenting abilities in this link is sparse. So far, only a small number of studies have shown that parenting abilities (i.e., positive discipline and maternal sensitivity) mediate the association of prenatal maternal depressive symptoms/stress with child behavioral outcomes in early childhood (Edwards and Hans 2016;Kok et al 2013). The mediating role of parenting abilities in the link between maternal anxiety during pregnancy and child behavioral/emotional outcomes has, however, not been studied so far.…”
mentioning
confidence: 99%